Structural biology of voltage-gated calcium channels - Xia Yao; Shuai Gao; Nieng Yan (Taylor & Francis Group, 2024)
ABSTRACTVoltage-gated calcium (Cav) channels mediate Ca2+ influx in response to membrane depolarization, playing critical roles in diverse physiological processes. Dysfunction or aberrant regulation of Cav channels can lead to life-threatening consequences. Cav-targeting drugs have been clinically used to treat cardiovascular and neuronal disorders for several decades. This review aims to provide an account of recent developments in the structural dissection of Cav channels. High-resolution structures have significantly advanced our understanding of the working and disease mechanisms of Cav channels, shed light on the molecular basis for their modulation, and elucidated the modes of actions (MOAs) of representative drugs and toxins. The progress in structural studies of Cav channels lays the foundation for future drug discovery efforts targeting Cav channelopathies.